Invasive Meningococcal Disease in the Vaccine Era - Nadel, Simon; Ninis, Nelly (Frontiers in Pediatrics, 2018)
Infection with the meningococcus is one of the main causes of meningitis and septicaemia worldwide. Humans are the only natural reservoir for the meningococcus which is found primarily as a commensal inhabitant in the nasopharynx in ~10% of adults, and may be found in over 25% of individuals during adolescence. Prompt recognition of meningococcal infection and early aggressive treatment are essential in order to reduce mortality, which occurs in up to 10% of those with invasive meningococcal disease (IMD). This figure may be significantly higher in those with inadequate or delayed treatment. Early administration of effective parenteral antimicrobial therapy and prompt recognition and appropriate management of the complications of IMD, including circulatory shock and raised intracranial pressure (ICP), are critical to help improve patient outcome. This review summarizes clinical features of IMD and current treatment recommendations. We will discuss the evidence for immunization and effects of vaccine strategies, particularly following implementation of effective vaccines against Group B meningococcus.